A Head-To-Head Comparison of Benzbromarone and Allopurinol on the Risk of Type 2 Diabetes Mellitus in People With Asymptomatic Hyperuricemia - Shih-Wei Lai; Shih-Wei Lai; Kuan-Fu Liao; Kuan-Fu Liao; Yu-Hung Kuo; Cheng-Li Lin; Cheng-Li Lin; Chiu-Shong Liu; Chiu-Shong Liu; Bing-Fang Hwang (Frontiers Media S.A., 2021)
Objective: The study aimed to thoroughly address the influence of benzbromarone and allopurinol on the risk of the development of type 2 diabetes mellitus (T2DM) in people with asymptomatic hyperuricemia.Methods: We conducted a retrospective cohort study to examine the 2000-2015 national dataset containing all claims data of 23 million beneficiaries in Taiwan. Subjects who already had diabetes mellitus, gout-related diseases, and any cancer prior to the index date were excluded. Asymptomatic hyperuricemia was defined as subjects taking urate-lowering drugs who never had a gout flare. Subjects aged 20-84 with asymptomatic hyperuricemia who had benzbromarone prescriptions were selected as the benzbromarone group. Sex-matched and age-matched subjects with asymptomatic hyperuricemia who had allopurinol prescriptions were identified as the allopurinol group. The maximum follow-up duration was set as 5 years in our study. The outcome was set as subjects who had a new diagnosis of T2DM. The incidence density of T2DM was calculated in the benzbromarone and allopurinol groups. The hazard ratio (HR) and 95% confidence interval (CI) for T2DM was utilized to estimate the association between medications and the risk of T2DM.Results: The incidence of T2DM among benzbromarone users was significantly lower than that of allopurinol users (7.91 versus 8.48 per 100 person-years, incidence rate ratio = 0.93, and 95% CI = 0.87-0.99). After adjustment for co-variables, the adjusted HR of T2DM would be 0.91 (95% CI = 0.85-0.98 and p = 0.008) in benzbromarone users as compared to allopurinol users.Conclusion: There is a small but statistically significant risk reduction of developing T2DM in people with asymptomatic hyperuricemia taking benzbromarone as compared to those taking allopurinol during 5 years of follow-up. It indicates a future research direction for the use of individual urate-lowering drugs on the prevention of T2DM in the general population.